2020
DOI: 10.1016/j.ihj.2020.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of short-term prognosis of fragmented QRS complexes in patients with acute myocardial infarction in two groups that received invasive and fibrinolytic therapy

Abstract: Background Studies have shown that the primary causes of death in patients with acute coronary syndrome are arrhythmias and heart failure. The aim of this study is to evaluate the short-term prognosis of fragmented QRS (f-QRS) in patients with acute myocardial infarction (MI). Methods This study was a prospective and longitudinal analytic study performed on all patients with acute MI admitted to Rasht Heshmat Hospital Emergency during 2018–2019. Serial Electrocardiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…However, it has been reported that an ECG shows abnormalities in only 3.2% to 8.6% of patients with clinically silent CS [1]. fQRS appears as multiple spikes within the QRS complex and has been reported to be associated with ventricular arrhythmic events (VAEs) in patients with myocardial infarction, Brugada syndrome, and hypertrophic cardiomyopathy [9][10][11]. However, the significance of fQRS in cardiac sarcoidosis has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that an ECG shows abnormalities in only 3.2% to 8.6% of patients with clinically silent CS [1]. fQRS appears as multiple spikes within the QRS complex and has been reported to be associated with ventricular arrhythmic events (VAEs) in patients with myocardial infarction, Brugada syndrome, and hypertrophic cardiomyopathy [9][10][11]. However, the significance of fQRS in cardiac sarcoidosis has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%